Molecular Study of FLT3 gene mutations in Acute Myeloid Leukemia from Pakistan : Correlation with clinicopathological parameters. - Faiz, Mariam; Rashid, Farzana (Asian Pacific Journal of Cancer Biology, 2019)
Introduction: FLT3 mutations are common genetic changes reported to have prognostic significance in acute myeloid leukemia (AML). Bone marrow/peripheral blood samples of 63 AML Pakistani patients were collected and DNA was isolated. Materials and Methods: The FLT3 internal tandem duplication (ITD) and the D835 activating mutation in the tyrosine kinase domain (TKD) were analyzed by polymerase chain reaction (PCR). Results: Among 63 AML patients, 42 were males and 21 were females with male to female ratio 2.1:1. The age ranged between 15 to 75 years with a median age of 32 years. AML-M2 was the predominant French-American-British (FAB) subtype (32%) followed by M3 (27%), M4 (19%), M5 (6.3%) and M1 (6.3%). The incidence of FLT3/ITD and TKD was 22% and 6.3% respectively. Majority of the FLT3/ITD mutation were detected in AML-M4 (38%) patients while D835 mutation was common in both FAB M1, M2. Presence of mutation was significantly associated with age but significance was not achieved for hyperleukocytosis. Conclusion: This study constitutes the first report from Pakistan reporting significant presence of FLT3/ITD mutations in our adult AML patients with different FAB subtypes Molecular mutation analysis in different cytogenetic groups with follow-up is required to understand the pathogenesis of leukemias and their role as a valuable prognostic marker in our patients.